Comparison of Open Source Geographic Information System (GIS) Technology for Information System Development Tools - Sidiq, Miftahul (PT ARRUS Intelektual Indonesia, 2025)
This study aims to compare Open source Geographic Information System (GIS) tools that can be used as supporting tools for the development of Information Systems (IS), including Web Apps, Mobile Apps, Web Services, and other applications. The research examines seven subjects, each evaluated based on five key objectives. These objectives include spatial data processing features, data API capabilities, basemap features, ease of use, licensing costs, and data loading performance. The GIS tools analyzed in this study are Geoserver, Map Server, QGIS Server, PostGIS, and GeoNode. The expected outcome of this research is to provide comprehensive information on the strengths and weaknesses of each technology, aiding decision-making in selecting the most suitable technology or combination of technologies for specific use cases